OC-006 LAPAROSCOPIC TOTALLY EXTRA-PERITONEAL REPAIR OF BILATERAL INGUINAL HERNIAS WITH A LARGE SINGLE MESH: A SINGLE CENTER STUDY WITH MINIMUM 5 YEARS FOLLOW UP. (13th October 2022) - Shaltiel, T; Grassi, C; Esepkina, O; Issa, N
Abstract: Background: Laparoscopic totally extraperitoneal (TEP) surgery with a single large mesh is currently the technique of choice for repair of bilateral inguinal hernias in our institution. Most surgeons use two meshes for the TEP repair. We present our experience with a single mesh repair. Material & Methods: Records of all patients who had bilateral inguinal hernia and underwent bilateral laparoscopic TEP repair at our institution, 2010–2016, were retrospectively reviewed. We excluded patients who had a conversion to transabdominal intraperitoneal or open approach. Results: A total of 470 patients were identified. The median age of patients was 56 (IQR 1–3; 41–66) years and median BMI was 25.9 (IQR 1–3; 23.1–28.1). 18.7% of the cohort (88 patients) had previous abdominal surgery and 39 patients (8.41%) had a recurrent inguinal hernia. Median length of operation was 63 (IQR1–3; 48–89) minutes. Operative complication were bleeding (0.4%) and bladder injury (0.2%). Post operative complications occurred in 32 patients; among the complications were seroma (2.6%), hematoma (2.1%), surgical site infection (0.4%) urinary retention (1.5%) and intestinal obstruction (0.2%). Median length of hospitalization was 1 day (IQR1–3; 1–2). After a median follow up of 102 months, 36 patients had a recurrence. 20 patients (4.3%) had a re-operation for recurrent inguinal hernia. Post-operative groin pain was present in 48 patients. Conclusion: The use of a large single mesh is an effective and safe technique for TEP repair of bilateral inguinal hernias. The recurrence rate and prevalence of post-operative pain is consistent with the results reported by others.